# How do you solve #5(x − 1) = 3(x + 2) − 7#?

##### 1 Answer

Jun 3, 2017

#### Answer:

Answer:

#### Explanation:

1) Distribute the

#5x - 5 = 3x + 6 - 7#

2) Combine like terms on the right side. **YOU DON'T CHANGE WHAT IS ON THE LEFT SIDE!**

#5x - 5 = 3x - 1#

3) Add 5 to **BOTH SIDES** to keep the equation balanced.

#5x = 3x + 4#

4) Subtract 3x from **BOTH SIDES** to keep the equation balanced.

#2x = 4#

5) Divide 2 on **BOTH SIDES** to keep the equation balanced.

#x = 2#

And you are done!